Relationship between body composition, leg strength, anaerobic power, and on-ice skating performance in Division I men's hockey athletes - Potteiger, J. A.; Smith, D. L.; Maier, M. L.; Foster, T. S. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine relationships between laboratory tests and on-ice skating performance in division I men's hockey athletes. Twenty-one men (age 20.7 ± 1.6 years) were assessed for body composition, isokinetic force production in the quadriceps and hamstring muscles, and anaerobic muscle power via the Wingate 30-second cycle ergometer test. Air displacement plethysmography was used to determine % body fat (%FAT), fat-free mass (FFM), and fat mass. Peak torque and total work during 10 maximal effort repetitions at 120°/s were measured during concentric muscle actions using an isokinetic dynamometer. Muscle power was measured using a Monark cycle ergometer with resistance set at 7.5% of body mass. On-ice skating performance was measured during 6 timed 89-m sprints with subjects wearing full hockey equipment. First length skate (FLS) was 54 m, and total length skate (TLS) was 89 m with fastest and average skating times used in the analysis. Correlation coefficients were used to determine relationships between laboratory testing and on-ice performance. Subjects had a body mass of 88.8 ± 7.8 kg and %FAT of 11.9 ± 4.6. First length skate-Average and TLS-Average skating times were moderately correlated to %FAT ([r = 0.53; p = 0.013] and [r = 0.57; p = 0.007]) such that a greater %FAT was related to slower skating speeds. First length skate-Fastest was correlated to Wingate percent fatigue index (r = -0.48; p = 0.027) and FLS-Average was correlated to Wingate peak power per kilogram body mass (r = -0.43; p = 0.05). Laboratory testing of select variables can predict skating performance in ice hockey athletes. This information can be used to develop targeted and effective strength and conditioning programs that will improve on-ice skating speed.